The Influence of Interim Auditor Reviews on the Association of Returns with Earnings - Manry, David; Tiras, Samuel L.; Wheatley, Clark M. (The Accounting Review, 2003)
The Securities and Exchange Commission now requires auditors to review interim earnings reports on a timely basis. Previously, auditors could perform this review retrospectively, as part of the year-end audit. We investigate whether timely reviews are likely to increase the relevance and reliability of reported earnings, as reflected by the extent to which the earnings-return relation is contemporaneous. We find that when the auditor reviews interim earnings on a timely basis, the association between quarterly returns and earnings (and between quarterly returns and unexpected earnings) is predominantly contemporaneous. When the auditor reviews interim earnings retrospectively, however, the association between quarterly returns and earnings is not entirely contemporaneous; with retrospective reviews, returns lead interim earnings. We conclude from these findings that timely reviews increase the likelihood that accounting earnings reflect economic events contemporaneously with returns.